Breaking Through Barriers: Factors That Influence Behavior Change Toward Leadership for Women in Academic Medicine - Pelfrey, Clara M.; Cola, Philip A.; Gerlick, Joshua A.; Edgar, Billie K.; Khatri, Sumita B. (Frontiers in Psychology, 2022)
Under-representation of women in leadership at Academic Medical Centers (AMCs) is a known challenge such that, in 2018, women made up only 18% of department chairs. AMCs are addressing the dearth of women leaders through targeted programming to create leadership pipelines of qualified women. The FLEX Leadership Development Program at the Case Western Reserve University (CWRU) School of Medicine prepares women faculty for increased leadership opportunities. FLEX includes the opportunity to leverage executive coaching to accomplish individual goals. The FLEX program has the explicit goal of increasing the number of women in visible leadership positions in academic medicine and health sciences. Semi-structured interviews were conducted with 25 graduates from FLEX cohorts (2012-2018). Participants reflected diversity in academic rank, terminal degree, racial/ethnic background, years of employment, and institutional affiliation. Interviews consisted of eight questions with additional probes to elicit lived experiences. Analysis consisted of two-stage open- and axial-coding of interview transcripts to understand: What factors facilitated behavior change following FLEX training? The factors that facilitated behavior change following participation in the FLEX Program revealed five overarching themes: 1) Communication skills; 2) Self-Efficacy; 3) Networking; 4) Situational Awareness; and 5) Visioning. FLEX graduates reported achieving both personal and professional growth by drawing upon peer networks to proactively seek new leadership opportunities. These results suggest that the enduring benefits of the FLEX Program include improved communication skills, expanded situational awareness and relational capacity, greater self-efficacy, and self-confidence, improved networking with an understanding of the value of networking. All these factors led FLEX graduates to have greater visibility and to engage with their colleagues more effectively. Similarly, FLEX graduates could better advocate for themselves and for others as well as paying it forward to mentor and train the next generation of faculty. Finally, participants learned to re-evaluating their goals and their career vision to be able to envision themselves in greater leadership roles. The five factors that strongly influenced behavior change provide valuable constructs for other programs to examine following leadership development training. Ongoing studies include examining successful leadership position attainment, personal goal attainment, and measuring changes in leadership self-efficacy.